Preparation of high-performance epoxy materials with remarkable negative thermal expansivity. (April 2023) - Zhang, De-Hao; Li, Yang; Kamara, Gibrilla; Long, Lingliang; Yan, Wei-Cheng
Highlights: Epoxy materials with large negative thermal expansivity was achieved. Negative thermal expansion (NTE) performance can be well regulated. Improvements of thermal stability and mechanical properties of the prepared NTE epoxy material were achieved. Effects of eight-membered carbocyclic unit and Nano-TiO2 were evaluated. Molecular simulation of crosslinking process was performed. Abstract: In this study, a simple but effective strategy to synthesize epoxy materials with negative thermal expansion (NTE) performance was proposed. The thermal expansion coefficient of epoxy material was turned from positive (154.5 ppm/K) to negative (−492.6 ppm/K) by introducing eight-membered carbocyclic (EMCC) structure into bisphenol-A epoxy resin system. The NTE performance can be well regulated by controlling the ratio of EMCC-polyamide. Molecular simulation was also carried out, suggesting that the system with the 15 wt% EMCC-polyamide mass fraction gives the lowest energy as compared to those with 7.5 and 10 wt%. Improvements of thermal stability and mechanical properties of the synthesized negative thermal expansion epoxy material were achieved by further composited with nano-TiO2 . With the combination of EMCC unit and nano-TiO2, the prepared epoxy materials can possess good hardness and stiffness, meanwhile, have acceptable flexibility and toughness. The modified epoxy materials were successfully used as coating materials for the encapsulation of monocrystalline silicon. This study provides a new strategy for the preparation and regulation of polymer composites with excellent NTE performance. Graphical abstract: Image, graphical abstract